Updating the Rules for Online Content Dissemination Legislative Options of the European Union and the Digital Services Act Proposal - D. Cole, Mark (Schriftenreihe Medienforschung der Landesanstalt für Medien NRW, 2021)
The current legal framework for online content dissemination has proven insufficient to effectively combat illegal content. The Commissions' proposal for an EU 'Digital Services Act' aims to update the horizontal framework for intermediaries and create a safe online environment. However, as far as content mediation is concerned, European fundamental rights and values require that the specificities of media law must be taken into account. This study, conducted by the Institute of European Media Law (EMR) on behalf of the Media Authority of NRW, describes the current legal framework and the DSA proposal, and provides a comprehensive assessment from the perspective of media law, complemented by alternative proposals for further improvement.